2012
DOI: 10.1186/2008-6695-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response of asymmetric systems with linear and non-linear viscous dampers

Abstract: The free vibration characteristics, such as fundamental frequency and mode shape of stiffened plates employing standard finite element analysis, are investigated in this paper. The parametric study is presented for free vibration characteristics of stiffened plates with various parameters, such as type, orientation and number of stiffeners, boundary conditions and aspect ratio of plates and stiffener depth to plate thickness ratio. Typical mode shapes are also presented for clamped square eccentrically stiffen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Among the different types of fluid viscous dampers, non-linear viscous dampers (velocity coefficient less than one) are preferred because of the limiting peak value of damper forces at large damper velocities [64,65], while in the case of a linear damper, the damping force increases with the damper velocity. Non-linear viscous dampers have a variable damping force that can be tuned to match the specific vibration characteristics of a structure.…”
Section: Dampersmentioning
confidence: 99%
“…Among the different types of fluid viscous dampers, non-linear viscous dampers (velocity coefficient less than one) are preferred because of the limiting peak value of damper forces at large damper velocities [64,65], while in the case of a linear damper, the damping force increases with the damper velocity. Non-linear viscous dampers have a variable damping force that can be tuned to match the specific vibration characteristics of a structure.…”
Section: Dampersmentioning
confidence: 99%
“…[2][3][4] Using the control strategy of structures to prevent damage or reduce its value is also a good solution to this problem. 5,6 In this context, various passive control equipment, including tuned mass dampers, [7][8][9][10][11][12][13][14] viscous dampers, [15][16][17][18] and base isolations [19][20][21][22] have been applied to reduce the effects of torsion in the asymmetric structures. Also, dynamic responses of asymmetric structures have been significantly reduced by the use of different equipment and methods of active [23][24][25][26][27] and semi-active [28][29][30] control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…MR dampers are semi-active control dampers and hence are more effective than their passive counterparts [16]. Others have examined the response of a linear elastic, one-story building with linear and non-linear viscous dampers [17]. It was shown that non-linear viscous dampers are more effective at reducing the responses as well as in decreasing the effects of torsional coupling.…”
Section: Introductionmentioning
confidence: 99%